2006
DOI: 10.1080/13651820410016660
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation in surgical practice

Abstract: Mechanisms of the acute phase response are discussed including the individual parameters and local changes that take part. Mechanisms involved in failure of the gut barrier are presented and include changes in gut barrier permeability, effects on gut-associated immunocompetent cells, and systemic implications. As examples of HPB disease, mechanisms of the acute phase response and potential ways of intervention in obstructive jaundice and acute pancreatitis are discussed. Nutritional pharmacology and lessons le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…Obstructive jaundice is a clinical entity that has a high morbidity and mortality rate due to septic complications, and it is associated with an impaired systemic and local immune function [ 1 5 ]. A key pathophysiological function of obstructive jaundice is bodily disruption of the intestinal barrier functionality, which consists of more than one protecting mechanism [ 2 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obstructive jaundice is a clinical entity that has a high morbidity and mortality rate due to septic complications, and it is associated with an impaired systemic and local immune function [ 1 5 ]. A key pathophysiological function of obstructive jaundice is bodily disruption of the intestinal barrier functionality, which consists of more than one protecting mechanism [ 2 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids can have a nourishing impact on the mucosa of the intestine by reducing the passage of enteric bacteria into the intestinal epithelium through detergent activities and protective effects against adherence and restrictions of bacterial overgrowth. Consequently, the decreased flow of bile in obstructive jaundice results in BT, and in this situation, it is important to support the immune function of the host [ 5 , 9 ] It has been reported that honey results in expansive range movement against gram-positive and -negative microorganisms [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…An immunoenhancing diet (IED) can modulate both the hyperinflammatory and compensatory phases associated with surgery5. O‐3FAs, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are important constituents of immunonutrition owing to their effects on eicosanoid balance.…”
Section: Introductionmentioning
confidence: 99%
“…In cholestasis emerging after biliary obstruction, the RES seems to be ruined and phagocytic function is depressed. Kupffer cell activation plays a basic role at the beginning of an efficacious immune response (5,8,11,17).…”
Section: Discussionmentioning
confidence: 99%
“…Two points play a key role in the pathophysiology of septic complications. One is physical disruption of the intestinal barrier function and the other is an impaired immune system, especially the reticuloendothelial system (RES) and metabolic functions of the liver because of cholestasis (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%